English Language Learning Challenges in Remote Areas: A Case Study of Rural Schools - Irma Juliana Ekawati Janis; Dewi Veranita Rajagukguk; Grace Ireni Gaitedy (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This research aimed to investigate the challenges of English learning in remote areas at SMP Terpadu Negeri 12 Nafar, Kepulauan Aru, Maluku. The research employed a qualitative case study approach involving twenty students as the participants. The data was collected through questionnaires and semi-structured interviews. The questionnaire data was analyzed using a Likert scale, while the interview data was analyzed descriptively to support and strengthen the research findings. The result revealed that the students experienced several significant challenges in learning English. The findings showed that geographical access factors had the highest influence on students’ learning challenges with a percentage of 90%, followed by environmental and social factors at 85%, student’s factors which included motivation and ability at 80%, facilities and infrastructure at 65%, and teachers and teaching methods at 30%. Limited facilities, lack of support in environmental, low learning motivation and geographical isolation significantly affected students’ English learning experiences. This research suggests the importance of improving the educational support, learning resources, and teaching strategies to enhance English learning in rural and remote schools